The electromagnetic fine-structure constant in primordial nucleosynthesis revisited - Meißner, Ulf-G.; Metsch, Bernard Ch; Meyer, Helen (The European physical journal. A, Hadrons and nuclei, 2023)
We study the dependence of the primordial nuclear abundances as a function of the electromagnetic fine-structure constant α , keeping all other fundamental constants fixed. We update the leading nuclear reaction rates, in particular the electromagnetic contribution to the neutron-proton mass difference pertinent to β -decays, and go beyond certain approximations made in the literature. In particular, we include the temperature-dependence of the leading nuclear reactions rates and assess the systematic uncertainties by using four different publicly available codes for Big Bang nucleosynthesis. Disregarding the unsolved so-called lithium-problem, we find that the current values for the observationally based 2 H and 4 He abundances restrict the fractional change in the fine-structure constant to less than 2 % , which is a tighter bound than found in earlier works on the subject.